Students’ Perception of Game-Based Learning Using Kahoot! In Learning English - Fitria Gita Rahmadani; Tampung N Saman; Bahing (The Study Program of English Education of Palangka Raya University, 2024)
This study aims to evaluate students' perceptions of the use of Kahoot! application in English learning and its impact on students' learning motivation in terms of its effectiveness and competitiveness,. This study used observation, questionnaire, and interview methods with 23 students in class XI Language of SMAN 1 Palangka Raya. The results showed that most students agreed that Kahoot! is an effective tool for English learning in class. Kahoot! increased their learning motivation through the Game-Based Learning (GBL) method, including competitive feeling, interactive learning, visual experience, fun learning, and customization. The results of this study show that Kahoot! is an effective learning tool to increase students' motivation in English learning. In addition, the use of Kahoot! can improve students' mood and help them understand the material more quickly also students feel more creative and enjoy learning due to the interactive and fun nature of the platform. The implication of this study is that students respond more positively to interactive, visual and fun learning media such as Kahoot! Teachers can consider using Kahoot! routinely in learning to improve students' motivation and learning outcomes. With this, Kahoot! is expected to be the learning tool whose influence has been sought.